Characterization of Ag-Cu-S Thin Layers Formed on Low Density Polyethylene Film - Ingrida ANCUTIENĖ; Remigijus IVANAUSKAS; Nijolė KREIVĖNIENĖ (Medžiagotyra, 2011)
The Ag-Cu-S layer formed on PE demonstrated a wide variation in thickness. The cross-section showed the average thickness of sulfide layers on PE increase from 1.9 mm to 5.6 mm with the increase in the sulfurization time and from 1.9 mm to 3.9 mm with the increase of treating time in the solution of copper salts. The electronic micrographs of the sulfide layers indicate the creation of an irregular but continuous base of small dendrites and agglomerates. With the increase in the sulfurization time and treating time in copper (II/I) salt solution observed an increase of the agglomerates size. Energy dispersive spectroscopy results indicate that modified layers are poor in copper (0.5 at. % - 1.5 at. %). The atomic ratios of Ag/Cu/S, calculated from the quantification of the peaks (excluded C and O elements) give the values (%) of 8.3:1.5:4.4, 8.7:0.5:4.3 and 23:1.2:10.9, respectively. In all cases, energy dispersive spectroscopy measurements revealed the modified layers are nearly stoichiometric Ag2S. http://dx.doi.org/10.5755/j01.ms.17.3.584